Implementation and Validation of the Optimized Space Diversified Antenna Arrays for Extended FM-RF Propagation - Fernando Nuena Mangubat Jr.; Naomi Asendiente Bajao; Victorino Hermosilla Patindol; Florieza Mendoza Mangubat (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2026)
FM broadcast antennas come in many shapes and sizes, but the dipole remains one of the most widely used designs because of its simple structure and reliable performance. For long-distance FM transmission, multiple antennas are often stacked to improve coverage and produce a stronger, more consistent radiation pattern. In these configurations, each antenna bay is adjusted to achieve the desired directional characteristics, and identical bays generate the same azimuth radiation pattern when installed as an array. The researchers designed and optimized a low-power FM broadcast antenna that performed better than the conventional design while meeting the required polarization and radiation pattern specifications based on antenna simulation results. However, because of the restrictions brought about by the COVID-19 pandemic, the antenna was never fabricated or tested using an antenna analyzer. As a result, its performance had only been evaluated through simulation. This study bridges that gap by fabricating the proposed antenna and validating its performance under actual operating conditions. The measured parameters obtained from an antenna analyzer were compared with the simulation results, including measurements taken after the antenna was mounted on a steel tower to determine the effects of the installation environment. The results showed close agreement between the simulated and measured values. The fabricated antenna produced a low reflection coefficient and a voltage standing wave ratio (VSWR) close to 1.0, indicating efficient power transfer and good impedance matching. Field measurements using the Deva Radio Explorer-Mobile FM Radio Analyzer also confirmed stronger signal performance than the conventional antenna. These findings demonstrate that the proposed design performs well not only in simulation but also in practical deployment, making it a viable option for low-power FM broadcasting.